Biodiversity in a changing climate : linking science and management in conservation - Root, Terry Louise; Hall, Kimberly R., 1967-; Herzog, Mark Paul, 1969-; Howell, Christine A. (Christine Ann) (University of California Press, 2015)
"Building upon the rapidly-growing body of literature documenting how natural systems are responding to, and are at risk from, human-induced climate change, this book provides case-study examples of how a diverse range of species and ecological systems in California are changing with the climate. These case studies originate from multiple ecological fields (genetics, population biology, habitat studies, community ecology, landscape ecology, paleobiology) and are framed by chapters describing approaches and tools for climate-adaptation planning, reviewing climate impacts and biological responses, and encouraging the use of historical data. This framing emphasizes the need for partnerships between researchers and resource managers in addressing climate-related challenges, and highlights how communication strengthens these partnerships with 'conversations' between chapter authors and managers. Such connections help move advances in science from research reports to 'on the ground' changes that help protect species, and support all life"--Provided by publisher